Satisfaction of Persons with Physical Disabilities at Family-Style Restaurants in Kuala Terengganu - Bakar Hamzah, Nur Anis Fatihah Abu; Anuar, Nur Amira Syazani; Ghani, Fatimah Abd; Ramli, Noorazlin (Information Management and Business Review, 2025)
For people with disabilities (PWDs) to have the best possible dining experiences in restaurants, they require specialized accessibility. Nevertheless, some restaurant owners sometimes overlook this issue when offering suitable amenities for this particular group of patrons. Therefore, this study aims to identify physical key factors influencing individuals with physical disabilities at family-style restaurants in Kuala Terengganu, Malaysia. The physical key variables in this study include the respective space for parking facilities, the building’s design, the design of the dining area, and the family-style restaurant restroom specifications. 400 valid replies were analyzed using the Statistical Package for the Social Sciences (SPSS), and the analysis’s findings demonstrate the importance of each suggested variable. The data was gathered in Kuala Terengganu using an online questionnaire and some paper surveys, in compliance with the restriction on physical distances. According to this study, the design of buildings, the design of the dining area, and restroom specifications are the three independent factors that impact customer satisfaction. Future academicians and other interested parties can learn more about the topic of this study. Government agencies and food service providers will also benefit from the insights as they plan and operationalize better in the future to increase consumer satisfaction.